Low charge overpotential of lithium-oxygen batteries with metallic Co encapsulated in single-layer graphene shell as the catalyst. (December 2016) - Tu, Yunchuan; Li, Haobo; Deng, Dehui; Xiao, Jianping; Cui, Xiaoju; Ding, Ding; Chen, Mingshu; Bao, Xinhe
Abstract: Rechargeable lithium-oxygen (Li–O2 ) battery has triggered tremendous attention as a promising candidate power source for portable electronics and light vehicles. Until now, a critical scientific challenge facing Li–O2 battery is the high charge overpotential due to the sluggish oxygen evolution reaction (OER) on the oxygen electrode, which results in low energy efficiency and poor cyclability. Here, we demonstrated that nitrogen-doped single layer graphene shell encapsulating non-precious metal Co can be used as a highly efficient catalyst for Li–O2 batteries. The catalyst showed significantly enhanced OER catalytic activity, with a charge overpotential of 0.58 V, which was remarkably lower compared with the corresponding N-free graphene encapsulating metal, metal oxide and metal-free carbon materials. DFT calculations revealed that the nitrogen dopants and enclosed metal clusters can synergistically modulate the electronic properties of the graphene surface, resulting in a dramatic reduction of the overpotentials. This study provides the possibility of the rational non-precious metal electrocatalysts designing for Li–O2 batteries. Graphical abstract: High-performance lithium-oxygen batteries with low overpotentials was realized by using nitrogen-doped single-layer graphene shell encapsulating metallic Co as the catalyst, where metallic Co and nitrogen dopants can synergistically modulate the electronic properties on the graphene surface, resulting in a dramatic reduction in the voltage gap of Li–O2 batteries by changing the thermodynamic free energies of the intermediates of each reaction steps and affecting the potential difference between these steps. Highlights: N-doped single layer graphene shell encapsulating metal Co was used as oxygen electrode catalyst for Li–O2 batteries. The Co catalyst shows superior OER catalytic activity, with a charge overpotential of only 0.58 V. Enclosed Co and nitrogen dopants can synergistically modulate the electronic properties on the graphene surface.